(untitled) (Abstracta, 2021)
Artigos publicados 2020 - P367-2020 à P415-2020 Eventos publicados 2020 - P416-2020 Correções 2020 - Co003-2020 Artigos publicados 2021 - P001-2021 à P031-2021 Correções 2021 - Co001-2021 à Co002-2021 Material Editorial 2021 - Ma001-2021 Defesas de Dissertações do IFGW - D001-2020 à D002-2020 Defesas de Teses do IFGW - T001-2020